Piecemeal stewardship activities miss numerous social and environmental benefits associated with culturally appropriate ways of caring for country. (15th January 2023) - Larson, Silva; Jarvis, Diane; Stoeckl, Natalie; Barrowei, Ryan; Coleman, Bessie; Groves, David; Hunter, Joshua; Lee, Maria; Markham, Michael; Larson, Anna; Finau, Glenn; Douglas, Michael
Abstract: Prior research has identified both the contribution that people make to nature and the contribution that nature makes to people (by enhancing wellbeing) – with clear conceptual models to describe the interactions. Prior research has also made a clear case for incorporating insights from multiple perspectives and knowledge systems when seeking to better understand this interactive system. What is lacking, is guidance on how to operationalise some of these ideas to provide bespoke advice to environmental managers. Arguably, we have an adequate, albeit imperfect, understanding of how to operationalise (measure, value and/or otherwise account for) some parts of the conceptual model. There is, for example, abundant literature that describes different ways of valuing Ecosystem services, and a growing body of literature that describes and quantifies the ecological benefits of various stewardship activities, which will subsequently also generate an indirect benefit to people (since improved ecological conditions will improve Ecosystem services). In comparison, we know relatively little about the way in which stewardship activities directly benefit people – and it is on this gap that our paper focuses. We partially fill that knowledge gap by first reaching out to and learning from some of Australia's First Nations People. Key learnings underscore the inter-connectedness of the system, and the need for resource managers to not only monitor the extent and condition of natural system but also the extent and condition of an inextricably connected human system, in addition to the human-nature interactions. We clearly identify ways in which those insights can be used to improve and extend accounting frameworks, such as SEEA Ecosystem Accounts developed by the United Nations that are often used by natural resource managers. In so doing, we generate new insights about Indigenous stewardship ( Caring for Country) and methods of accounting for and monitoring stewardship activities. As such, our work provides a practical illustration of one way to populate conceptual models with 'real world' data that also incorporates different world views, to support decision makers for improved social and environmental outcomes. Highlights: Linear models of nature-human system omit the benefits from people via stewardship. Piecemeal stewardship activities generate only piecemeal benefits. Stewardship done the 'right way' benefits the environment AND the people involved. Stewardship the 'right way' by the right people maximises human wellbeing. Accounting systems could be enhanced to better show benefits of Caring for Country .